Pedagogical perspective of social learning in the metaverse: A case study of computer graphics programming - Aleksić Veljko V. (University of Kragujevac - Faculty of Pedagogy, Užice, 2023)
The potential of using the metaverse as a contemporary digital educational environment for social learning presents a current pedagogical challenge. Considering that social learning presents a powerful model for acquiring new knowledge and skills, it is valid to observe it as an effective complement topromoting learning and development in various contexts. Given the limited empirical evidence on social learning effects in the metaverse environment, this study aimed to examine the impact of students' activities in this digital environment on their perception of the learning platform and learning outcomes. The results indicate that the pedagogical component played a significant role in students' intention to use the metaverse, but that technology did not. The study also revealed that students who participated in online activities achieved significantly better results in specific areas of computer graphics programming. The research emphasizes the need for deepening the understanding of complex social learning and adapting pedagogy for learning in the metaverse, especially the characteristics that would support collective intelligence.